A educação catarinense entre 1930 e 1945 : história das políticas educacionais a partir da imprensa e da legislação - Soligo, Valdecir (2008)
The purpose of this paper is to contribute with the productions about the History of Educational Politics in the State of Santa Catarina within the years 1930 and 1945. The general objective is focused around the investigation and exam of political and educational aspects of Santa Catarina, relating to the interference of the Federal Government in the educational policy of the State and the relations between the coastal region and country-side, making the role of legislation and the state and regional press in the construction of political, pedagogical and physical structure of the education in the state stand out. And the central point is the nationalization and illiteracy. The involvement of the political elite and the population of Santa Catarina in the creation of plans of education is analyzed, whether this participation is direct or indirect, through the press or the members of the parliament. Therefore, the educational legislation and Santa Catarina press are research sources , whose content can be found in documents at the Public Filing Department of the Lesgislative Assembly of the State of Santa Catarina and the Public State Library, both located in Florianópolis. These files present an immensurable richness, little-explored by researches developed so far. The temporal indenture established is justified by the fact that this period is one of the most representative of the national politics radicalization, involving inside elements, such as the revolution of 1930, the Constitution of 1934, the New State of 1937 among others; and outside elements such as the World s Capitalism Crisis of 1929, with its reflexes in the 1930 s and the Second World War initiated in 1939. Between 1930 and 1945, the political and social structures alternated and interfered in the educational politics, which reflect in later periods, on such influence that it somehow lasts until the present moment. Moreover, they face resistance similar to the ones occurring in the German colonization Centers or in country-side regions highly dependent on the family workers for agricultural production. In these conditions the expansion of public teaching was an instrument of combat against the influence of foreing cultures. In addition to that, the press of Santa Catarina reveals many diferences among regions of the state. While urban centers had a bigger attention of the public power, many villages and mountain range cities and west not even had enough schools. The research revealed that one of the biggest problems was the lack of teachers to work in the regions farther from the big urban centers, in the meantime these populations fought for the right of public education